2012
DOI: 10.1021/ja310351e
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dearomative Rearrangement of Biaryl Phosphine-Ligated Pd(II) Complexes

Abstract: A series of monoligated L•PdII(Ar)X complexes (L = dialkyl biarylphosphine) have been prepared and studied in an effort to better understand an unusual dearomative rearrangement previously documented in these systems. Experimental and theoretical evidence suggest a concerted process involving the unprecedented PdII-mediated insertion of an aryl group into an unactivated arene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 93 publications
6
74
0
Order By: Relevance
“…A nearly identical species bearing a related ligand and also possessing η 3 -binding of the dearomatized ring to the Pd center has been previously reported [14]. This species likely does not form by oxidative addition of 1 •Pd(0) to CDCl 3 followed by a dearomative rearrangement similar to that reported for other Pd(II) complexes of 1 [7,9] because the CDCl 2 and Pd center are bound to opposite faces of the lower ring of the ligand. Instead, a carbene mechanism is proposed to be involved in the formation of 3 [14].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A nearly identical species bearing a related ligand and also possessing η 3 -binding of the dearomatized ring to the Pd center has been previously reported [14]. This species likely does not form by oxidative addition of 1 •Pd(0) to CDCl 3 followed by a dearomative rearrangement similar to that reported for other Pd(II) complexes of 1 [7,9] because the CDCl 2 and Pd center are bound to opposite faces of the lower ring of the ligand. Instead, a carbene mechanism is proposed to be involved in the formation of 3 [14].…”
Section: Resultssupporting
confidence: 66%
“…CD 2 Cl 2 , CDCl 3 , and toluene-d 8 were purchased from Cambridge Isotopes in sealed ampules and used without further purification. Preparations of AdBrettPhos ( 1 ) [7], t BuBrettPhos ( 6 ) [8], RockPhos ( 7 ) [8], 2 [1], 5 [9], 12 [10], 13 [9], 14 [10], and 17 [11] have been previously described. The t BuXPhos ( 8 ) used in this work was purchased from Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…These ligands form well-defined bidentate mono-P-liganded Pd(0) species [45][46][47][48] with the structures formally corresponding to the 12-electron Pd-P(III) active catalysts of the SM reaction (Scheme 2, AC). The active catalyst is extremely reactive and readily undergoes oxidative addition reaction with aromatic halides to form intermediates with a welldefined structure I [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…[17] Thus,t he auxiliary ligands largely affect the s-p state of indole complexes.Itshould be noted that the positive charge of the indole ligand in the p( Thus,o ur experimental and theoretical results showed that there is the s-p continuum in indole-Pd II complexes.The s-p continuum has been previously observed in the h 1 -arenemetal complexes, [18,19] although the pure s-complexes of arenes (Wheland-intermediate-type) have been rarely identified due to the insufficient charge transfer between the arene ligand and am etal center.…”
mentioning
confidence: 94%